Exploring Cognitive Variability in Interactive Museum Games - George E. Raptis (Heritage)
Understanding how cognitive differences shape visitor behavior in digital heritage experiences is essential for designing inclusive and engaging museum technologies. This study explores the relationship between cognitive level and interaction behavior, affective responses, and sensor-based engagement using a publicly available dataset from a digital museum game. Participants (N = 1000) were categorized into three cognitive levels (Early, Developing, and Advanced), and their data were analyzed across three domains: user interaction behavior, affective and performance states, and sensor-based interaction measures. Our findings suggest that sensor-level interactions are more sensitive indicators of cognitive differences than observable behavior or inferred affect. This work contributes to the heritage HCI field by highlighting the potential for cognitively adaptive systems that personalize the museum experience in real-time, enhancing accessibility, engagement, and learning in cultural settings.